Obstructing Non-refluxing Megaureter Secondary to Ectopic Ureter - Dr. Sanjay P. Dhangar (SP’z Series New Insights on Urology and Urological Research Part I, 2022)
Megaureter is a nonspecific term that refers to a variety of anomalies associated with grossly dilated diameter of ureter. One such malformation is an ectopic ureter. Any ureter, single or duplex, that does not penetrate the trigonal portion of the bladder is referred to as an ectopic ureter. Any ureter with a diameter of 7-8 mm2 is considered a megaureter. Among neonates and early children, a megaureter is a common cause of obstructive uropathy. It is four times more frequent in boys than in girls, and it affects <25% of patients bilaterally. Girls are more likely to have an ectopic ureter. The left ureter is 1.6±4.5 times more likely than the right to be implicated. In this case, a 12-year-old female child had an ectopic ureter that resulted in a secondary obstructing non-refluxing megaureter.